2010
DOI: 10.1161/strokeaha.109.561795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Intensive Blood Pressure-Lowering Treatment on the Growth of Hematoma and Perihematomal Edema in Acute Intracerebral Hemorrhage

Abstract: Background and Purpose-The Intensive Blood Pressure Reduction In Acute Cerebral Haemorrhage Trial (INTERACT) study suggests that early intensive blood pressure (BP) lowering can attenuate hematoma growth at 24 hours after intracerebral hemorrhage. The present analyses aimed to determine the effects of treatment on hematoma and perihematomal edema over 72 hours. Methods-INTERACT included 404 patients with CT-confirmed intracerebral hemorrhage, elevated systolic BP (150 to 220 mm Hg), and capacity to start BP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(139 citation statements)
references
References 23 publications
3
132
0
4
Order By: Relevance
“…The Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT) randomized 404 patients with ICH to intensive blood pressure lowering treatment (systolic blood pressure (SBP) < 140 mmHg) compared with traditional management (target SBP < 180 mmHg). This study demonstrated a reduction in hematoma growth at 24 hours with intensive BP lowering (14 versus 26 percent), however, this finding did not achieve statistical significance after adjustment for initial hematoma volume and time from ICH onset to head CT [35][36][37]. There was also no effect of treatment on clinical outcomes at 90 days [36].…”
Section: Blood Pressure Management In Ichmentioning
confidence: 53%
See 1 more Smart Citation
“…The Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT) randomized 404 patients with ICH to intensive blood pressure lowering treatment (systolic blood pressure (SBP) < 140 mmHg) compared with traditional management (target SBP < 180 mmHg). This study demonstrated a reduction in hematoma growth at 24 hours with intensive BP lowering (14 versus 26 percent), however, this finding did not achieve statistical significance after adjustment for initial hematoma volume and time from ICH onset to head CT [35][36][37]. There was also no effect of treatment on clinical outcomes at 90 days [36].…”
Section: Blood Pressure Management In Ichmentioning
confidence: 53%
“…The mean arterial pressure (MAP) is often elevated in patients with ICH and may provide a continued force for bleeding [35][36][37]. However, an increased MAP may also be necessary to maintain cerebral perfusion and aggressive lowering the arterial pressure could result in ischemia and worsen neurologic injury.…”
Section: Intracranial Hemorrhagementioning
confidence: 99%
“…Not only do we understand better its potential complications (i.e. the spot sign can predict greater chances of hematoma expansion) but also are beginning to treat it better with more aggressive control of hypertension in the acute phase, as suggested to be safe in the INTERACT trial (15) . This approach is now under further investigation in the INTERACT 2 trial (16) .…”
Section: Treatment Of Hemorrhagic Strokementioning
confidence: 99%
“…An acute hypertensive response in patients with intracerebral hemorrhage is common 1 and may be associated with hematoma expansion and increased mortality. 2,3,4 The second Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial 5 (INTERACT2) included patients with spontaneous intracerebral hemorrhage who had a systolic blood pressure of 150 to 220 mm Hg within 6 hours after symptom onset. The rate of death or disability among patients randomly assigned to intensive reduction in the systolic bloodpressure level, with a target systolic blood pressure of less than 140 mm Hg within 1 hour, was nonsignificantly lower than the rate among those assigned to guideline-recommended treatment, with a target systolic blood pressure of less than 180 mm Hg, with the use of a variety of antihypertensive medications (absolute difference, 3.6 percentage points; P = 0.06).…”
mentioning
confidence: 99%
“…5 We designed the Antihypertensive Treatment of Acute Cerebral Hemorrhage II (ATACH-2) trial 6 to determine the efficacy of rapidly lowering the systolic blood-pressure level in patients in an earlier time window after symptom onset than that evaluated in previous trials. 4,5,7 The trial was based on evidence that hematoma expansion and the rate of subsequent death or disability might be reduced with very early and more aggressive reduction in the systolic blood-pressure level 8,9 among persons at high risk owing to a high systolic blood-pressure level (≥170 mm Hg10 to ≥200 mm Hg 11 ) at presentation.…”
mentioning
confidence: 99%